(untitled) (Bangladesh Journal of Livestock Research, 2021)
This research was aimed to improve the egg production performances and to estimate the selection response of fifth generation (G5) of deshi white (Rupali) and white breasted black (Nageswari) duck genotypes through an individual selection program. All the ducks were reared in an open sided duck house. Diet containing 17.5% CP and 2750 Kcal ME/kg and fresh water provided twice daily in the morning and evening. Individual egg production was recorded from each duck. After 40 weeks of age, female ducks were selected on the basis of selection index and selection differences, selection intensity and responses were also measured. Egg weight, egg production and feed intake were recorded and FCR, egg mass was calculated. All recorded data were analyzed by SAS and differences were determined by DMRT. The selection criteria of fifth generation (G5) of both duck genotypes were studied. As a result of selection, age at sexual maturity (day), egg weight (g) and egg production % were expected to improve by -1.63d, 0.60g, 1.01% and -0.85day, 0.39g, 0.47% for Rupali and Nageswari ducks, respectively. Egg mass was significantly (p<0.05) higher in Rupali (40.24g) than Nageswari (37.55g) duck whereas, egg weight was not significantly differ in both genotypes. Egg production in Rupali and Nageswari duck was 65.41% and 62.74%, respectively. Rupali ducks were significantly (p<0.05) consumed more feed (134.54 g) than Nagesswari ducks (126.23 g). The FCR was significantly (p<0.05) better in Rupali (3.34) than Nageswari (3.61) ducks. The egg quality results showed that egg shell thickness of Rupali duck was significantly (p<0.05) higher than Nageswari. Higher values for albumen width (p<0.05) was also found in Rupali (65.03mm) than Nageswari (59.11mm) duck egg. On the other hand shape index, albumen index, yolk index and haugh unit were not found significantly different in both genotypes but the yolk color score of Nageswari found highest score than Rupali duck egg. Proximate composition of eggs was not significantly different of both duck genotypes. Based on the results it is revealed that Rupali duck was better in terms of egg weight, egg mass and egg production, but starting lay egg is earlier in Nageswari than Rupali duck. Bang. J. Livs. Res. Vol. 27 (1&2), 2020: P. 15-23